Stuart Woods' Blown away - Battles, Brett; Woods, Stuart (Woods, Stuart. Teddy Fay novel, 2025)
"Teddy Fay whisks away to join Peter and Hattie Barrington in Palm Springs. But his hope for a relaxing vacation vanishes when he attends a prominent actor's annual birthday party, where he witnesses a heated squabble between two women, only for one of them to turn up dead the next day. Teddy investigates who might be lurking in the shadows and uncovers a web of intrigue involving a sinister plan to take over a cutting-edge energy company. If he doesn't act fast, valuable secrets risk falling into the wrong hands, but more importantly innocent lives could be in jeopardy"--